Edukasi Bijak Konsumsi Gula Berbasis Media Animasi Gambar untuk Mencegah Diabetes Mellitus pada Remaja di SMA Kesatrian 2 Semarang - Ulinnuha Nur Riza; Abrori, Abrori; Iwan Ardian (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Background: Diabetes Mellitus is a non-communicable disease with an increasing prevalence, including among adolescents. Excessive sugar consumption is one of the major risk factors. Preventive efforts can be carried out through health education using engaging media, such as animation-based media, to improve adolescents’ knowledge regarding Diabetes Mellitus prevention.us. Methods: This study employed a pre-experimental design with a one group pretest–posttest approach. The sample consisted of 37 tenth-grade students of Kesatrian 2 Senior High School Semarang selected based on inclusion and exclusion criteria. The research instrument was a knowledge questionnaire consisting of 20 true/false statements. Data were analyzed using the Wilcoxon Signed Rank Test to determine differences in knowledge levels before and after the intervention. Results: The results of the study showed an increase in the level of knowledge of adolescents after being given education on wise sugar consumption based on animated media. Before being given education, respondents in the category of not understanding were 40.54% and those in the category of understanding were 59.46%. After being given education based on animated media, respondents in the category of not understanding decreased to 8.11% and those in the category of understanding increased to 91.89%. The results of the Wilcoxon test showed a Z value = -3.878 with a p-value = 0.000 (p < 0.05), which means there was a significant change and increase in the level of knowledge before and after the intervention.